The architecture of multi-level governance of economic sectors - Renate Mayntz (Max Planck Institute for the Study of Societies, 2007)
In the age of globalization, many economic sectors are addressed not only by the policies of national, but also of international institutions. Using three cases of highly internationalized sectors of the German economy - international tourism, telecommunications, and the pharmaceutical industry - the paper tries to spell out and explain the differences in the governance architecture of these economic sectors. The main differences identified concern the prevalent purpose or goals of governance; the prevalent governance instruments; the relative importance of agencies at different territorial levels; and the prevalence of public, private, or mixed forms of governance. These differences are interrelated and reflect differences between sectoral economies. In the light of the comparison, the relationship between different levels in a multi-level governance structure is discussed, with a view to the extent and nature of coordination that exists between them. Both the architecture and the regimes of multi-level governance are shaped by attempts to cope with conflict, and manifest the endurance of conflicts that cannot be resolved once and for all.
Keywords: 300; Regulierung; Governance-Ansatz; International; Multinationales Unternehmen; Tourismuswirtschaft; Telekommunikationsgesellschaft; Pharmazeutische Industrie; Deutschland